Metallic WN plasmonic fabricated g-C3N4 significantly steered photocatalytic hydrogen evolution under visible and near-infrared light. Issue 24 (9th November 2022) - Tahir, Warisha; Ullah, Sami; Ullah, Ikram; Li, Jing-Han; Ling, Cong; Lu, Xiao-Jie; Qian, Xiao-Jun; Wang, Gang; Pan, Yueyin; Xu, An-Wu
Abstract : Energy level diagram and charge transfer mechanism of WN/CN- x plasmonic photocatalysts. Abstract : Semiconductor based photocatalysts are hardly employed to harvest broadband spectral light from the visible to near-infrared (NIR) light region due to bandgap limitations. Metallic and metal-like materials as photocatalysts are known to overcome this limitation through a plasmonic effect that can efficiently promote photocatalytic activity by converting the visible-NIR light photon energy into hot-electron energy. These energetic hot electrons undergo interband transition and transfer to adjacent semiconductors through an interfacial charge-transfer transition, thus inducing a photocatalytic reaction. Herein, we report a WN/g-C3 N4 nanohybrid photocatalyst constructed from plasmonic WN NPs and graphitic carbon nitride (g-C3 N4 ) nanosheets, a novel WN/CN photocatalyst for efficient photocatalytic H2 evolution by water splitting in the visible light and NIR light regions. Owing to the strong interfacial interaction and well-suited band alignment between g-C3 N4 and metal-like WN, the optimal WN/CN-1 sample (1 wt% WN) achieved an efficient photocatalytic hydrogen evolution rate of 72.17 μmol h −1 with an apparent quantum yield of 6.23% at λ = 420 nm, which is about 4 times higher than that of bare g-C3 N4 (17.17 μmol h −1 ). Notably, the developed WN/CN-1 photocatalyst also exhibits a hydrogen evolution rate of 16.32 μmol h −1 under NIR irradiation with an AQY of 0.46% at λ = 720 nm. In contrast, no hydrogen production is observed on bare g-C3 N4 under NIR light photoirradiation ( λ = 720 nm). The photocatalytic charge transfer transition mechanism of the plasmonic WN/CN nanocomposite is proposed, which is supported by density functional theory calculations. In general, this study provides a new creative approach to designing and developing other novel plasmonic antenna/reactor nanohybrids for plasmon-mediated chemical transformation by solar light.